2016
DOI: 10.1021/acs.jpcb.6b03475
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Replacement Mechanism in Molecular Beacons Encoded for the Detection of Cancer Biomarkers

Abstract: Signaling properties of a fluorescent hairpin oligonucleotide molecular beacon (MB) encoded to recognize protein survivin (Sur) mRNA have been investigated. The process of complementary target binding to SurMB with 20-mer loop sequence is spontaneous, as expected, and characterized by a high affinity constant (K = 2.51 × 10(16) M(-1)). However, the slow kinetics at room temperature makes it highly irreversible. To understand the intricacies of target binding to MB, a detailed kinetic study has been performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Our calculations—performed using the UNAFold software—indicate that the target oligonucleotide (tDNA), complementary to the loop of SurMB, preferentially forms a stable small-loop hairpin structure instead of relaxing to a linear conformation. Figure 1 A presents the sequence and the most thermodynamically stable hairpin structure of SurMB-Joe, with negative Gibbs free energy of formation ΔG° SurMB-Joe = −4.26 kcal/mol [ 37 ]. The loop sequence of the probe was composed of an antisense oligonucleotide targeting the survivin mRNA region [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculations—performed using the UNAFold software—indicate that the target oligonucleotide (tDNA), complementary to the loop of SurMB, preferentially forms a stable small-loop hairpin structure instead of relaxing to a linear conformation. Figure 1 A presents the sequence and the most thermodynamically stable hairpin structure of SurMB-Joe, with negative Gibbs free energy of formation ΔG° SurMB-Joe = −4.26 kcal/mol [ 37 ]. The loop sequence of the probe was composed of an antisense oligonucleotide targeting the survivin mRNA region [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the attachment of a small quenching graphite nanoparticle (NP) to the end of a MB strand was applied by Piao et al [ 36 ]. Although the use of GO is gaining popularity in DNA sensing applications [ 39 ], the exact conformation of DNA strands has rarely been evaluated [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding demonstrates that the physicochemical properties of cGNS incorporating MB are not influenced by the sequence of MB. Considering the biological function of MB, it is important to evaluate the sequence specificity of MB and MB incorporated in cGNS for the hybridization 30 , 31 . The hybridization study indicated that the fluorescent recovery of both MB and MB incorporated in cGNS was specific for the target sequences (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that polycystin-1 co-localizes with E-cadherin at the cell-cell contacts, accelerating the recruitment of intracellular E-cadherin to reforming junctions [40]. These exosome proteins could be proposed as targets for the detection of a cancer biomarker [41,42,43]. …”
Section: Discussionmentioning
confidence: 99%